Serotonin transporter gene polymorphism in eating disorders: Data from a new biobank and META-analysis of previous studies. (18th May 2016) - Solmi, M.; Gallicchio, D.; Collantoni, E.; Correll, C.U.; Clementi, M.; Pinato, C.; Forzan, M.; Cassina, M.; Fontana, F.; Giannunzio, V.; Piva, I.; Siani, R.; et al.
Abstract : Objectives Growing interest focuses on the association between 5-HTTLPR polymorphism and eating disorders (ED), but published findings have been conflicting.Methods The Italian BIO.VE.D.A. biobank provided 976 samples (735 ED patients and 241 controls) for genotyping. We conducted a literature search of studies published up to 1 April 2015, including studies reporting on 5HTTLPR genotype and allele frequencies in obesity and/or ED. We ran a meta-analysis, including data from BIO.VE.D.A. – comparing low and high-functioning genotype and allele frequencies in ED vs. controls.Results Data from 21 studies, plus BIO.VE.D.A., were extracted providing information from 3, 736 patients and 2, 707 controls. Neither low- nor high-functioning genotype frequencies in ED patients, with both bi- and tri-allelic models, differed from controls. Furthermore, neither low- nor high-functioning allele frequencies in ED or in BN, in both bi- and triallelic models, differed from control groups. After sensitivity analysis, results were the same in AN vs. controls. Results remained unaltered when investigating recessive and dominant models.Conclusions 5HTTLPR does not seem to be associated with ED in general, or with AN or BN in particular. Future studies in ED should explore the role of ethnicity and psychiatric comorbidity as a possible source of bias.